Silver Nanoparticle-Incorporated Hydroxyapatite-Chitosan-PVP-Based Scaffold for Bone Tissue Engineering: Physicochemical Characterization, Antibacterial Activity, and In Vitro Ceftriaxone Release Study - Polash Chandra Karmakar; Monira Islam Chamely; Tusher -Al-Arafat; Marina Khatun; Naznin Akhtar; S. M. Asaduzzaman (Advances in Materials Science and Engineering)
The development of biocompatible scaffolds is rapidly growing in several fields of human health, particularly for the treatment of bone defects. In this study, silver nanoparticle (AgNPs)-incorporated hydroxyapatite (HA), chitosan (Chi), and polyvinylpyrrolidone (PVP)-based scaffolds were fabricated using the freeze-drying method for bone tissue engineering. Physicochemical properties such as porosity, density, swelling ratio, and biodegradability, as well as blood biocompatibility, brine shrimp lethality, antibacterial activities, FTIR-ATR, tensile strength, cytotoxicity, and SEM, were conducted. A study on the in vitro release of ceftriaxone (Cef), a routinely prescribed medication for treating osteomyelitis, was done. The selected scaffolds had desirable porosity, density, swelling capability, and biodegradation rate, which would meet the basic prerequisites for osteogenesis. The scaffolds showed qualitative and quantitative antibacterial activities against Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Scaffolds were minimally cytotoxic to brine shrimp and RBC biocompatible. FTIR analysis confirmed intermolecular interaction among components of scaffolds. Scaffold had a tensile strength of 2.9 ± 0.22 N/mm2 and a non-cytotoxic effect on Vero cell lines. Surface morphology, pore shape, and sizes (98–382 μm) were observed through SEM. The percentage of drug (Cef) loading was found to be 63.16 ± 4.85%. An initial burst release of Cef was 40.21 ± 1.50% in the first 24 h. A sustained release of Cef was observed after 4 days, and about 60.36 ± 2.38% was released within 14 days. Therefore, selected AgNPs-incorporated HA-Chi-PVP scaffold could be a potential aid for bone tissue engineering.